Extracorporeal Membrane Oxygenation for SARS-CoV-2 Acute Respiratory Distress Syndrome: A Retrospective Study From Hubei, China - Yang, Xiaobo; Hu, Ming; Yu, Yuan; Zhang, Xijing; Fang, Minghao; Lian, Yingtao; Peng, Yong; Wu, Lingling; Wu, Yongran; Yi, Jun; Zhang, Lu; Wang, Bing; et al. (Frontiers in Medicine, 2021)
Background: The data on long-term outcomes of patients infected by SARS-CoV-2 and treated with extracorporeal membrane oxygenation (ECMO) in China are merely available. Methods: A retrospective study included 73 patients infected by SARS-CoV-2 and treated with ECMO in 21 intensive care units in Hubei, China. Data on demographic information, clinical features, laboratory tests, ECMO durations, complications, and living status were collected. Results: The 73 ECMO-treated patients had a median age of 62 (range 33–78) years and 42 (63.6%) were males. Before ECMO initiation, patients had severe respiratory failure on mechanical ventilation with a median PO2/FiO2 of 71.9 [interquartile range (IQR), 58.6–87.0] mmHg and a median PCO2 of 62 [IQR, 43–84] mmHg on arterial blood analyses. The median duration from symptom onset to invasive mechanical ventilation, and to ECMO initiation was19 [IQR, 15–25] days, and 23 [IQR, 19–31] days. Before and after ECMO initiation, the proportions of patients receiving prone position ventilation were 58.9 and 69.9%, respectively. The median duration of ECMO support was 18.5 [IQR 12–30] days. During the treatments with ECMO, major hemorrhages occurred in 31 (42.5%) patients, and oxygenators were replaced in 21 (28.8%) patients. Since ECMO initiation, the 30-day mortality and 60-day mortality were 63.0 and 80.8%, respectively. Conclusions: In Hubei, China, the ECMO-treated patients infected by SARS-CoV-2 were of a broad age range and with severe hypoxemia. The durations of ECMO support, accompanied with increased complications, were relatively long. The long-term mortality in these patients was considerably high.